RelB/p50 regulates CCL19 production, but fails to promote human DC maturation. - Gasparini, C; Foxwell, B; Feldmann, M (2009)
DC, when fully matured are the APC best able to activate naïve T cells. Recently, we demonstrated using adenoviruses overexpressing IkappaBalpha and proteosome inhibitors that NF-kappaB is involved in DC activation, but the role of the individual subunits is still not clear. We investigated the role of the NF-kappaB subunits RelB and p50 in human DC activation using adenoviral vectors expressing RelB or p50. Nuclear RelB, in the form of RelB/p50, was active only in DC infected with both viruses, this induced the production of the soluble homeostatic chemokine CCL19, but not other homeostatic chemokines, particularly in LPS-matured DC. However, RelB/p50 did not affect the expression of costimulatory and antigen-presenting molecules, and increased the allogeneic mixed lymphocyte reaction only in LPS-matured DC. This enhanced mixed lymphocyte reaction is most likely due to enhanced CCL19 production, which sustains the interaction between mature DC and naïve T cells. In conclusion, we demonstrated that RelB/p50 was active only in DC expressing both RelB and p50, and induced CCL19 production, but not DC maturation.